Pemetaan Faktor Penyebab Kenakalan Siswa pada Jenjang Madrasah Ibtidaiyah di MI Babussalam Kecamatan Pasongsongan - Afina Wastyanti (Bahasa Indonesia, 2026)
ABSTRACT : Student bad behavior refers to behavior or actions that can cause problems, harm individuals or other people, and violate ethical and social standards. The purpose of this research is to determine the causes of naughty behavior in class IV Mi Babussalam students, and the types of mischief committed by class IV Mi Babussalam students. This research is qualitative in nature and involves the use of a case study model. This research was conducted at Mi Babussalam Pasongsongan Sumenep. This research focuses on student bad behavior (delinquency). Information collection includes interview notes, observation sheets, and documents. Data analysis is based on the Miles and Huberman model, with data collection as the main methodology for collecting information, presenting it as output, analyzing state-of-the-art data using quantitative methods, and drawing conclusions. The validity of the data was verified through source triangulation techniques. Research shows that student misbehavior includes behaviors such as fighting, teasing, and ignoring school policies. These bad actions are not only caused by the students themselves but can also be the result of the influence of their families or the surrounding environment, such as a poor environment, lack of attention from parents, and disharmony within the family. A common form of student bad behavior is causing the classroom environment to become chaotic or disorganized by using dirty words to manipulate their friends so that fights occur. To deal with student bad behavior, teachers and schools can use actions such as warnings, sanctions, and letters of agreement to students not to repeat this again. This is done with the aim of creating a deterrent effect that prevents bad behavior from occurring in the future. Preventing student misbehavior requires joint efforts between educators and families, as well as a review of school programs. Key Words: Delinquency, students, elementary school